Graduate medical education in anaesthesiology and COVID-19: lessons learned from a global pandemic. Issue 6 (1st December 2021) - Chu, Larry F.; Kurup, Viji
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose of review: The recent global pandemic has dramatically altered the anaesthesiology educational landscape in unexpected ways. It is important that we pause to learn from this crisis. Recent findings: Most resident trainees actively caring for COVID-19 patients present with probable or subclinical finding of post-traumatic stress disorder. Anaesthesia resident training programmes evolved to continue the mission of anaesthesia education in the face of institutional restrictions and evolving clinical crises. Summary: The recent global COVID-19 pandemic has illustrated how external stressors can cause significant disruption to traditional medical education pathways. Resilience to external disruptive forces in anaesthesia education include a willingness of leadership to understand the problem, flexibility in adapting to the needs of learners and instructors in the face of key challenges, deployment of technology and innovation-minded solution-finding where appropriate, and attention to Maslow's hierarchy of needs. Video abstract: http://links.lww.com/COAN/A77